Functional timing or rhythmical timing, or both? A corpus study of English and Mandarin duration - Wang, Chengxia; Xu, Yi; Zhang, Jinsong (Frontiers in Psychology, 2023)
It has been long held that languages of the world are divided into rhythm classes so that they are either stress-timed, syllable-timed or mora-timed. It is also known for a long time that duration serves various informational functions in speech. But it is unclear whether the two kinds of uses of duration are complementary to each other, or they are actually one and the same. There has been much empirical research that raises questions about the rhythm class hypothesis due to lack of evidence of the suggested isochrony in any language. Yet the hypothesis is still widely taken for granted and continues to be researched. Here we conducted a corpus study of English, an archetype of a stress-timed language, and Mandarin, an alleged syllable-timed language, to look for evidence of at least a tendency toward isochrony when much of the informational use of duration is controlled for. We examined the relationship between segment and syllable duration and the relationship of syllable and phrase duration in the two languages. The results show no isochrony tendency in English because that syllables are incompressible to allow stress-timing, and the reason behind is that segment duration is inflexible to allow variable syllable duration beyond its functional use. Surprisingly, however, Mandarin does show a small tendency toward both equal syllable duration and equal phrase duration. Additionally, the duration of pre-boundary syllables in English increases linearly with break index, whereas in Mandarin, the duration increase stops after break index 2, which is accompanied by the insertion of silent pauses. We conclude, therefore, timing and duration in speech are predominantly used for encoding information rather being controlled by a rhythmic principle.